Ragam Bahasa Pemelajar Bipa dalam Menggunakan Bahasa Indonesia Menurut Teori Speaking D Hymes: Indonesia - winar, Renanda; Nisa, Chana Khoirun; Febrian, Agnes Wahyu; Muzaki, Helmi (Hasta Wiyata, 2025)
Technology had a great influence on the dissemination of information. Such a Indonesian spread in the international arena has a major impact on the development of the language. The result of language development is an increase in vocabulary until the emergence variety of language. Variations of language helped the communication of speakers, so that they can be used according to the situation and conditions needed, including BIPA learners. But sometimes with the emergence of various languages, BIPA students have little difficulty distinguishing of using language according to their situation and conditions. The purpose of this study is to analyze the speech acts of BIPA learners with the analysis of D. Heymes' SPEAKING theory. The method used in this study is a qualitative descriptive method with a content analysis approach. In the results of the analysis, the author will describe the results of communication created by BIPA students using the SPEAKING method by focusing on the variety of languages contained in linguistic aspects. BIPA students also tend to use a variety of official or formal languages in every conversation in formal classes. However, BIPA students also use an unofficial language when talking to colleagues interspersed with English or their mother tongue.